INDONESIAN MILLENNIALS' NEEDS IN THE WORKPLACE A Case Study in: PT Akur Pratama - Devina Devina; Sapta Dwikardana (Business Administration Department - Universitas Katolik Parahyangan, 2019)
Recently the number of Millennials in the workplace is growing and soon projected to dominate the workforce. In the past, the companies succeeded in forcing their workforce to follow their principles. However, most of Millennials who have distinctive characteristics chose to leave the companies instead of being forced, which resulted in high turnover. The objective of this study is to explore Indonesian Millennials’ needs in the workplace that could contribute to their engagement and also could help to reduce turnover. This study used qualitative approach by interviewed eight participants who work at least 3 months at PT Akur Pratama. The result showed the most chosen factors as Millennials’ needs are coaching, teamwork, flexibility in hour, macro managing, develop relationship and fair compensation.Keywords: Millennials, Millennials’ characteristics, Millennials’ needs, engagement, turnover